SOSIALISASI SADAR HUKUM PENYALAHGUNAAN NARKOTIKA (Universitas Wijayakusuma Purwokerto, 2024)
Drug abuse is almost evenly distributed throughout Indonesia, starting from the household level, neighborhood association (RT), community association (RW), sub-district/village, sub-district, district/city, province, up to the national level. Even though the prevalence figure for drug abuse is relatively small, when converted to an equivalent figure, the average number of Indonesian people who abuse drugs is around 2 million people. In the period 2021 to 2023, drug users fell to 1.73 percent or around 3.3 million people. This means that in the last year, of the 10 thousand Indonesian population aged 15-64 years, there were 173 people who were exposed to drugs. Even though the ratio of drug abuse in Indonesia is still lower than the ratio at world level, this ratio has the potential to increase in the future if it is not anticipated or prevented with maximum efforts.